Current knowledge on biomarkers for contact sensitization and allergic contact dermatitis - Koppes, Sjors A.; Thierse, Hermann-Josef (Contact dermatitis, 2017)
Contact sensitization is common and affects up to 20% of the general population. The clinical manifestation of contact sensitization is allergic contact dermatitis. This is a clinical expression that is sometimes difficult to distinguish from other types of dermatitis, for example irritant and atopic dermatitis. Several studies have examined the pathogenesis and severity of allergic contact dermatitis by measuring the absence or presence of various biomarkers. In this review, we provide a non-systematic overview of biomarkers that have been studied in allergic contact dermatitis. These include genetic variations and mutations, inflammatory mediators, alarmins, proteases, immunoproteomics, lipids, natural moisturizing factors, tight junctions, and antimicrobial peptides. We conclude that, despite the enormous amount of data, convincing specific biomarkers for allergic contact dermatitis are yet to be described.
Gesehen am 29.05.2018